PEMBUATAN STRAP MASKER GUNA MENGEMBANGKAN KREATIFITAS LANSIA DI PANTI SOSIAL LANJUT USIA HARAPAN KITA KOTA PALEMBANG - Mahdiana, Yana; Wagisri, Wagisri; Indahsari, Indahsari; Sari, Arum Mayang; Iswandi, Iswandi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STISIPOL Candradimuka, 2023)
The activity of making mask straps was carried out as an effort to develop the creativity of the elderly in the midst of the Covid-19 pandemic. The activity was carried out at the Harapan Kita Orphanage, Palembang City, involving all elderly people of productive age. This activity aims to provide knowledge about the importance of using masks in protecting oneself from exposure to the COVID-19 virus. The method used in implementing activities is participatory with several stages including 1) Preparation stage, 2) Implementation stage consisting of providing materials and equipment; Training and education; Creative ideas from the elderly; Collaboration and discussion; Mini exhibition in the orphanage's meeting hall; and Giving appreciation to the elderly group, 3) Evaluation Stage. The results of the activity have a positive impact not only on the elderly but also on the administrators of social institutions. The success of this activity shows the extraordinary potential of elderly creativity in responding to global health challenges, while also strengthening social ties and well-being among the elderly.